A field manual for rapid vegetation survey and classification for general purpose - Gillison, A.N. (CIFOR and ACIAR, 2001)
The purpose of the manual is to introduce vegetation classification and survey to those with limited botanical or ecological experience. The kinds of people for whom the engaged in policy development to research workers, teachers and students. Apart from providing some background on classification concepts and procedures, section I is designed specifically to introduce the Vegclass windows based software that forms the core of the manual and to demonstrate how the software can be used to describe and classify vegetation for a range of purposes. The software facilitates both data entry and summary tables of the site physical, vegetation structural, plant species and plant functional data. It also includes a facility to produce graphs on demand and is capable of producing new, ecological measures of stand diversity based on plant functional attributes. Section ii contains a step by step introduction to data entry, coupled with an in-built, error checking protocol that will help introduce the new user to the methods used to compile, tabulate and analyse the data.